2017
DOI: 10.3892/ol.2017.6668
|View full text |Cite
|
Sign up to set email alerts
|

Influence of chronic inflammation on Bcl-2 and PCNA expression in prostate needle biopsy specimens

Abstract: The association between inflammation and cancer has been established in certain forms of human malignancies; however, its role in prostate cancer remains unclear. The present study investigates a possible association between chronic inflammation and the development of epithelial neoplasia in the prostate. Needle biopsy specimens were obtained from patients with serum prostate-specific antigen levels >4 ng/ml, evaluated for morphological findings, and immunostained for Bcl-2 and proliferating cell nuclear antig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…The MAPK family represents important signal transduction pathways involved in a variety of cellular responses, including inflammation 58 . Aberrant MAPKp38 and ERK pathways, 59,60 and Akt signaling 61 mediate growth of prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The MAPK family represents important signal transduction pathways involved in a variety of cellular responses, including inflammation 58 . Aberrant MAPKp38 and ERK pathways, 59,60 and Akt signaling 61 mediate growth of prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Under the influence of an inflammatory microenvironment, the molecular phenotype of injured epithelial cells becomes altered. For example, data from one of our recent related studies have shown an increase in the expression of Bcl-2, a marker of cell survival, in epithelial cells in areas adjacent to chronic inflammation [21]. We contend that as their molecular phenotypes change, these particular epithelial cells acquire neoplastic characteristics, changing into precursor cells of malignancy, which eventually proliferate uncontrollably and develop the ability to invade adjacent tissue.…”
Section: Figure 2 Needle Biopsy Specimen With Inflammatory and Adenomentioning
confidence: 97%
“…The pathophysiology of BPH is not clearly understood; however, its etiology is attributable to inflammatory [4] and/or oxidative stress [5]. Inflammation is known to have an association with excessive cell proliferation and death as compensatory hyperplasia could occur after cell death from chronic inflammation [6]. Oxidative stress also generates unstable chemical species that cause damage to mRNA, DNA, and proteins involved in cell death and proliferation [7].…”
Section: Introductionmentioning
confidence: 99%